Linn Meyers works 2004-2018 - Rodney, Seph; Walz, Jonathan F. (Radius Books, 2018)
Linn Meyers is best known for her intricate line-based paintings and drawings, and her large-scale installations. This book provides a comprehensive survey of site-specific wall drawings in museums and galleries since 2000, as well as the detailed preparatory drawings and plans created by the artist for these projects, plus recent paintings that inform, and are informed by, the site-specific works. Meyers's large projects require a great deal of endurance and involve drawing in the gallery space over the course of days, sometimes weeks or months, accumulating lines into dense and intricate compositions. The scale of these projects allows Meyers to respond to the existing architectural features, magnifying the wholly committed performativity of her process. On Meyers' exhibition for The Hammer Museum, Senior Curator Anne Ellegood wrote, "The sense of being present while viewing the work is also amplified at this larger scale, allowing viewers to experience the work not just visually but also physically. To see a wall drawing is to be surrounded by it and to feel oneself to be part of the work."
Co-published with The Columbus Museum and Jason Haam
Poem by Seph Rodney, and essays by Jonathan Frederick Walz and Anne Collins Goodyear
Accompanying booklet: Graph paper drawings
Keywords: Meyers, Linn -- 1968-; Geschichte 2004-2018; Malerei; Linie -- Motiv; Zeichnung; Meyers, Linn / Catalogs; Bildband